SISTEM PERAN SERTA PEMERINTAH BERSAMAMASYARAKAT DALAM PENANGANAN DAN PENGELOLAAN SAMPAH DI KABUPATEN TULANG BAWANG BARAT - Aris Pratama, Abizar (Universitas Sang Bumi Ruwa Jurai, 2022)
This take a look at goals to decide the position of neighborhood governments in empowering network organizations of waste control in Tulang Bawang Barat RegencyFrom an academic point of view, This research is expected to contribute to the development of government science. This research was conducted in the District of Tulang Bawang Barat, located at the Department of Plantation and Hygiene, using a qualitative research type. The research used is descriptive, data collection uses observation and interview techniques. Data were collected from various sources and the technique of determining informants was done by selecting informants who played a role and were technically involved in the role of local governments in empowering community groups to manage waste in Tulang Bawang Barat Regency. The Regent or Deputy Regent through the government's role in community empowerment: (1) Regulators (2) Dynamizers (3) Facilitators. And as for the factors supporting the role of government in community empowerment, namely: (1) local government aspirations (2) community support outside the region And inhibiting factors in community empowerment: (1) Limited understanding and knowledge of the community (2) Inadequate land availability.